Strategi Pemasaran Produk Premium Unilever Food Solutions “Knorr Chicken Powder” - Stivani, Cici; Nurlenawati, Netti; Triadinda, Dexi (STIE AMKOP, 2023)
This research is motivated by the growing competition in marketing similar products for Knorr chicken powder products. The aim of this research is to determine the marketing strategy implemented in the premium Unilever Food Solutions Knorr Chicken Powder product in increasing sales to face business competition. This research approach uses qualitative methods. Primary data was obtained directly through interviews and observation. Interviews were conducted with 5 informants. Secondary data was obtained from journal articles and library studies. The data that has been obtained is then analyzed using SWOT analysis. The research results showed that the company implemented a marketing strategy for Knorr Chicken Powder, namely using quality raw materials, prioritizing taste, maximizing production to fulfill consumer orders, delivering orders to customers who ordered in certain quantities. Suggestions that can be given for marketing Knorr chicken powder products are increasing marketing via social media and providing attractive promotions for consumers and offering cheaper discounts or promos. Keywords: Marketing Strategy_1, SWOT Analysis_2, Knorr Chicken Powder_3